Investigation of Charge Carrier Behavior in High Performance Ternary Blend Polymer Solar Cells. Issue 19 (8th July 2016) - Lee, Tack Ho; Uddin, Mohammad Afsar; Zhong, Chengmei; Ko, Seo‐Jin; Walker, Bright; Kim, Taehyo; Yoon, Yung Jin; Park, Song Yi; Heeger, Alan J.; Woo, Han Young; Kim, Jin Young
Abstract : This study demonstrates high‐performance, ternary‐blend polymer solar cells by modifying a binary blend bulk heterojunction (PPDT2FBT:PC71 BM) with the addition of a ternary component, PPDT2CNBT. PPDT2CNBT is designed to have complementary absorption and deeper frontier energy levels compared to PPDT2FBT, while being based on the same polymeric backbone. A power conversion efficiency of 9.46% is achieved via improvements in both short‐circuit current density ( J SC ) and open‐circuit voltage ( V OC ). Interestingly, the V OC increases with increasing the PPDT2CNBT content in ternary blends. In‐depth studies using ultraviolet photoelectron spectroscopy and transient absorption spectroscopy indicate that the two polymers are not electronically homogeneous and function as discrete light harvesting species. The structural similarity between PPDT2CNBT and PPDT2FBT allows the merits of a ternary system to be fully utilized to enhance both J SC and V OC without detriment to fill‐factor via minimized disruption of semi‐crystalline morphology of binary PPDT2FBT:PC71 BM blend. Further, by careful analysis, charge carrier transport in this ternary blend is clearly verified to follow parallel‐like behavior. Abstract : High performance ternary blend polymer solar cells including two donor polymers which share same polymeric backbone are demonstrated, and the charge carrier behavior is investigated as parallel bulk‐heterojunction. Real charge carrier behavior of ternary blends is firstly clarified via transient‐absorption spectroscopy. Two donors function as discrete light harvester, improving all photovoltaic parameters of the optimized ternary blend polymer solar cells.